Evaluation Of Accounting System Used By Small And Medium Scale Enterprises In Odo-Ona Nla/Idi Ayunre Ward - Elijah Adeyinka Adedeji; Zaynab, Shakrullah (Advances in Social Sciences Research Journal, 2020)
For a successful business endeavor, accounting is considered as the conduit and essential tool of achieving its target. It has always concerned itself with determining how a business is doing. The level of book keeping and accounting in SMEs have created many problems against the effective operation and accountability of these businesses. The study seek to determine the extent to which Small and Medium Scale Enterprises in Odo-Ona Nla/ Idi-Ayunre ward use accounting record keeping system in their business and to examine their perception towards accounting record keeping systems in their business. Achieving this objective, the paper adopts a quantitative and qualitative approach in which a semi structured questionnaire was used as the main data collection method. The researcher used purposive and simple random sampling techniques to reduce the possibility of research limitations. A total of 50 semi-structured questionnaires were distributed to various SMEs in Odo-Ona Nla/ Idi-Ayunre Ward at Oluyole Local Government in Ibadan. Forty-three (43) were returned and completely answered for the purpose of data analysis. The primary data collected were analyzed using the Statistical Package for Social Science (SPSS). The analyzed results are presented into graphical and descriptive representations such as tables, percentages, and graph. The findings indicate that majority of SMEs that maintain accounting records fail to keep complete accounting records and it also indicate that SMEs have many issues triggers to have negative attitudes in compliance to proper record keeping for their business, including cost associated, Time consuming and Tax avoidance. The paper concludes that a concerted effort should be made by the government and other stakeholders to set out proper guidelines for record keeping and proposes that SMEs owners be trained on key skills for records and information management which will enable them keep records of their business activities.